KARAKTERISTIK DINAMIS PERAN GANDA PEKERJA WANITA DI SEKTOR INFORMAL - M. TH HANDAYANI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2017)
Woman partsipation consists of tradition and transition roles.The transition or public role covers woman as a labor, member of society and development as a whole. meanwhile the tradition or domestic role includes women as a wife, mother and household manager. The study was carried out using an approach integrating the quantitative and qualitative research in the basis information about the context, subject and scale construction The result of the study shows that the phenomenon in the society is woman tends to work harder to earn money for the family and to express themselves. One indicator of woman role in national development can be seen from an increase in variety of woman job, it does not mean that the woman welfare increase automatically. The woman face discrimination, not only in domestic sector but also in public sector. Therefore, the dynamic characteristic of woman multifunction is important to be learned